Realism in Asia Volume One - Yeo, Wei Wei (National Gallery Singapore, 2011)
What is the place of realism in Asian art histories? What is the 'real'? How do reality and realism relate and differ? The six essays in this volume explore the manifestations of realism in Asian art, relating this art of description to issues of colonialism, world and civil wars, nation building, religion and contemporary culture in Asia.